Psychometric properties of the Pitcher adjective test to assess leadership (2013)
The psychometric properties of Pitcher Adjective Test, to assess leadership, were obtained. Participants were 400 health workers in the cities of Bogota, Cali, Bucaramanga and Barranquilla, in Colombia. By applying a logistic model, with difficulty and discrimination parameters, they were analyzed the properties of the items. The function of information of the test resulted more informative at the intermediate level (from -1.4 to 1.6), the indicators of difficulty and discrimination, were appropriate. A marginal reliability coefficient of.94 was obtained. Multiple correspondence analysis drew a two-dimension solution of leadership and by a latent class analysis, with a partial credit model, participants were classified into three leadership styles. According to this, it is concluded that psychometric properties are appropriate, and Pitcher Adjective Test is of interest, yielding a classification that does not correspond with those commonly used.